Pengaruh Faktor Demografi, Pengetahuan Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak - Putra, Iman Tri Yoga; Fauziati, Popi; Muslim, Resti Yulistia (Jurnal Ekonomi, 2019)
Taxes are the biggest source of revenue in the State Budget (APBN) each year. However, in 2015-2018 there was a decrease in the level of compliance of individual taxpayers in the Padang Satu KPP. This study aims to empirically examine and analyze the influence of demorafi factors, tax knowledge and tax sanctions on taxpayer compliance. This research uses the Convenience Sampling Design method. The method of collecting data through questionnaires, and then the data were analyzed using multiple linear regression analysis. Regression test results found that education level, tax knowledge and tax sanctions significantly influence tax compliance, while age, gender, marital status, type of work and income levels do not significantly influence tax compliance. Simultaneously demographic factor variables, tax knowledge and tax sanctions have a significant effect on taxpayer compliance.